Exact and Heuristic Approaches to the Maximum Capacity Representatives Problem - de Souza, Italos Estilon da Silva; da Silva, Mauro Roberto Costa; da Silva, Welverton Rodrigues; Schoeury, Rafael C. S. (Anais do Encontro de Teoria da Computação (ETC); 2018: Anais do III Encontro de Teoria da Computação, 2018)
This paper approaches the problem of finding the system of representatives of a family of disjoint sets. To solve this problem, three methods were used: integer programming, branch-and-bound, and the BRKGA metaheuristic. We observed that, in randomly generated instances, the branch-and-bound algorithm was the best exact method but it was surpassed by BRKGA for large instances.